PENJADWALAN PRODUKSI DENGAN IMPROVE ALGORITMA HODGSON - Akhsani Nur Amalia; Hady Soyan (JURNAL TEKNOSAINS KODEPENA, 2022)
The research was conducted to determine the production scheduling of Rodding System Point. The research is based on research that has been conducted by M. Syafaruddin Mahaputra (2020). This research was conducted using the Improve Hodgson Algorithm which considers the turnaround time for nine machines. The results showed that the Improve Hodgson Algorithm job completion can be done for 835.73 hours without delay. Scheduling with Improve Hodgson's Algorithm produces better scheduling than job sequencing with SPT rules.